ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGANKEJADIAN GINGIVITIS PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS TALANG TEGAL - -, hartati; -, rusmini; waluyo, bambang try (LPPM STIKES MUHAMMADIYAH GOMBONG, 2011)
Gingivitis is a mild inflammation of gum tissue caused by the accumulation of plaque. Gingivitis can occur at any age, but is prone to pregnantwomen. During pregnancy periode, esrogen and progesterone will increase, it will cause permeability of blood vessel and high risk of minor infection. The aim of this study to analyze factors associated with the occurrence of gingivitis in pregnant women at Puskesmas Talang Tegal. This type of research is analytic correlation with cross sectional approach. The sample in this study was 60 respondents with accidental sampling technique, and test using logistic regression analysis. The test result showed that there was a significant correlation between the factors plaque (p = 0.00), dental caries (p = 0.03), and gestational age (p = 0.00), on the incidence of gingivitis in pregnant women at Puskesmas Talang Tegal, while the factors that were not associated with the occurrence of gingivitis in pregnant women was factor irreguler arrangement of teeth (p = 0.73), and oral hygiene (p = 0.64), the most dominant factor was the plaque (p = 0.00 and wald = 12.00). Factors associated with the occurrence of gingivitis in pregnant women in the Puskesmas Talang Tegal are plaque, dental caries, and gestational age, with a more dominant factor that is plaque with OR = 24.24 which means that pregnant women with a plaque on the teeth will exposed 24 times to the risk of gingivitis compared with pregnant women without plaque on her teeth. Keywords : Analysis of the factors, the incidence of gingivitis, pregnant women